Young Adults Undergoing CABG; A Multicenter Study (Bangladesh Journal of Medical Science, 2024)
Objective: The  aim  of  this  study  is  to  describe  the  population of  young  adults  suffering  from  Coronary  Artery Disease  (CAD)  and  requiring  coronary  artery  bypass grafting  (CABG),  and  to  assess  early  outcomes. And to  identify  risk  factors  in  young  patients  undergoing CABG which is a major public health concern.Materials and Methods: This  is  a  Cross-sectional  study,  designed  as  an observational/descriptive  study,  conducted  with  the non-probability  method  i.e.  based  on  the  subjective judgment  of  the  researcher  rather  than  the  random selection. The study population will be recruited from five  different  hospitals  of  Karachi.  These  hospitals are selected with the consideration to the massive inflow of the patients. The Research tool that is going to  be  used  in  this  study  will  account  for  participant’s previous data, personal and family history as provided by  the  patient  at  the  time  of  procedure.  The  sample population  of  this  study  will  be  the  patients  who underwent elective CABG respectively. Patients aged 55 years or less undergoing CABG of both gender will be included.Result: Our  study  spots  Mild  to  Severe  stresses  in  subjects diagnosed  with  fatal  Myocardial  Infarction.  Along with huge changes in other biochemical markers.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 808-811